Rosiglitazone and a β3-Adrenoceptor Agonist Are Both Required for Functional Browning of White Adipocytes in Culture - Merlin, Jon; Sato, Masaaki; Chia, Ling Yeong; Fahey, Richard; Pakzad, Mohsen; Nowell, Cameron J.; Summers, Roger J.; Bengtsson, Tore; Evans, Bronwyn A.; Hutchinson, Dana S. (Frontiers in Endocrinology, 2018)
The recruitment of brite (or beige) adipocytes has been advocated as a means to combat obesity, due to their ability to phenotypically resemble brown adipocytes. Lineage studies indicate that brite adipocytes are formed by differentiation of precursor cells or by direct conversion of existing white adipocytes, depending on the adipose depot examined. We have systematically compared the gene expression profile and a functional output (oxygen consumption) in mouse adipocytes cultured from two contrasting depots, namely interscapular brown adipose tissue, and inguinal white adipose tissue, following treatment with a known browning agent, the PPARγ activator rosiglitazone. Prototypical brown adipocytes readily express uncoupling protein UCP1, and upstream regulators including the β3-adrenoceptor and transcription factors involved in energy homeostasis. Adipocytes from inguinal white adipose tissue display maximal UCP1 expression and mitochondrial uncoupling only when treated with a combination of the PPARγ activator rosiglitazone and a β3-adrenoceptor agonist. In conclusion, brite adipocytes are fully activated only when a browning agent (rosiglitazone) and a thermogenic agent (β3-adrenoceptor agonist) are added in combination. The presence of rosiglitazone throughout the 7 day culture period partially masks the effects of β3-adrenoceptor signaling in inguinal white adipocyte cultures, whereas including rosiglitazone only for the first three days promotes robust β3-adrenoceptor expression and provides an improved window for detection of β3-adrenoceptor responses.